Subtitling Strategies of Colloquial Expressions in Madame Web (2024) on Netflix - Zefanya Yacub; Nur Utami Sari’at Kurniati; Jordy Satria Widodo (Journal of Pragmatics Research, 2026)
Colloquial language frequently appears in contemporary films, making it challenging for translators to convey natural meaning and contextual implications across different languages and cultures. This study examines the subtitling strategies employed to translate colloquial expressions in Madame Web (2024), available on Netflix. The research focuses on identifying the types of colloquial expressions produced by the main female characters and analyzing the strategies employed by the translator in transferring meaning from English into Indonesian. A qualitative descriptive approach was adopted, drawing upon Gottlieb’s (1992) subtitling strategy framework and Partridge’s (1954) classification of colloquial forms. The data were collected through observation and note-taking, examining the utterances of the main characters in both the source language and their translated subtitles. Among the fifty-four colloquial expressions identified, seven out of Gottlieb’s ten strategies were observed, with paraphrasing used most frequently. The findings suggest that the translator tends to adapt the meaning to ensure the message remains natural and easily comprehensible to the target-language audience. Furthermore, the most frequent colloquial forms found were phrasal verbs and single words, reflecting a conversational style typical of native speakers in informal contexts. Overall, the findings suggest that the translator strives to maintain language appropriateness and clear meaning when translating expressions that lack direct Indonesian equivalents.